Analysis of the US Business Environment - Cook, Gina, 1970-; Machková, Hana; Sedláčková, Helena; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
In the last five years, the US has experienced a significant number of unprecedented events, many of which will have long-term impact on its business environment. Given this fact and the rapid pace of change in the world today, there is a new imperative for understanding and managing these complex dynamics and associated emergent risks. This dissertation, therefore, focused on analyzing the current state of the US business environment; the analysis creates a basis for further examination of the various aspects of the studied problems. The author undertook a comprehensive environmental scan, using a broad set of information resources, in order to look at its present status and the factors affecting it as well as the perceived level of risk. During this process, the author also attempted to verify whether the current method of PEST analysis is still a relevant and useful tool given today's complex, intertwined and quickly evolving global business environment. The first chapter is devoted to the theoretical background of information seeking and environmental analysis as well as classifying international business risks. Chapter two takes a broad look at the US macro economy, including the following areas: Political, Legal, Economic, Socio-Cultural and Technological. Chapter three is a business application, and the bulk of its content is devoted to the specifics of the current US business environment; the perceived risks affecting it are also investigated. Final conclusions are drawn based on the research conducted.
Vedoucí práce: Hana Machková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: mezinárodní ekonomické vztahy [obor disert. práce]; disertace; dissertations